2013
DOI: 10.1080/07391102.2013.787025
|View full text |Cite
|
Sign up to set email alerts
|

Identification of antagonists to the vasotocin receptor sub-type 4 (VT4R) involved in stress by molecular modelling and verification using anterior pituitary cells

Abstract: The vasotocin receptor family is homologous to the mammalian vasopressin G-protein coupled receptor (GPCR) family. The vasotocin receptor 2 (VT2R) and 4 (VT4R) have recently been shown to play important role(s) in the neuroendocrine regulation of stress in birds. A homology-based structural model of VT4R of the domestic chicken, Gallus gallus, was built using the sophisticated SYBYL-X suite. The structure of VT4R built with and without extra- and intracellular unstructured loops showed a seven-helix transmembr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Their conclusion was that the arginine vasopressin V1aR signal acts as an inhibitory system to suppress the NPY orexigenic action via the central nervous system and that blockade of the V1aR lead to increased food intake due to enhanced NPY sensitivity [23]. Our data utilizing an effective antagonist for the mammalian V1aR, SR-49059 [30] has shown it to be efficacious for blocking the chicken VT4R in vitro [11] and in vivo results of the current study. Due to the significant decrease in plasma CORT when SR-49059 was administered prior to immobilization compared to stressed birds given saline ICV, and the increased CORT plasma levels in birds given NPY compared to saline or SR-49059 administered control groups suggest that SR-49059 effectively blocked the VT4R and attenuated its activation due to inhibition of the binding of neuropeptides released by the stress procedure immobilization or central injection of the peptide NPY.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Their conclusion was that the arginine vasopressin V1aR signal acts as an inhibitory system to suppress the NPY orexigenic action via the central nervous system and that blockade of the V1aR lead to increased food intake due to enhanced NPY sensitivity [23]. Our data utilizing an effective antagonist for the mammalian V1aR, SR-49059 [30] has shown it to be efficacious for blocking the chicken VT4R in vitro [11] and in vivo results of the current study. Due to the significant decrease in plasma CORT when SR-49059 was administered prior to immobilization compared to stressed birds given saline ICV, and the increased CORT plasma levels in birds given NPY compared to saline or SR-49059 administered control groups suggest that SR-49059 effectively blocked the VT4R and attenuated its activation due to inhibition of the binding of neuropeptides released by the stress procedure immobilization or central injection of the peptide NPY.…”
Section: Discussionsupporting
confidence: 53%
“…Data obtained in broiler chicks, gallus gallus, four to five weeks of age, have shown that administration of antagonists of the mammalian vasopressin V1aR have likewise been effective in blocking the avian VT4R that has been proposed to be equivalent to the mammalian V1aR based upon its sequence homology [28], Genbank ACCN ABV24997) and key amino acid residues at specific sites that confer specificity to vasopressin-like residues [8,29]. Indeed Jayanthi et al (2014) showed that molecular models of both the Manning compound and SR-49059 were effective in displaying effective binding values in an analysis utilizing a 3D computer-based model built for the avian VT4R as well as an in vitro assay comprising chicken pituitary cells where the same two receptor blockers inhibited the expression of POMC hnRNA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations